VD_FINDINFO Pron / 2012 / 16 vom 23. Januar 2012 - VD Tribunal cantonal (2012)
TRANSACTION JUDICIAIRE, FRAIS JUDICIAIRES, DÉPENS | 109 CPC (CH), 122 al. 1 let. a CPC (CH), 241 al. 2 CPC (CH), 241 al. 3 CPC (CH), 65 al. 2 TFJC (2010), 67 al. 2 TFJC (2010)